IMPACT OF ASSET MANAGEMENT RATIO ON FINANCIAL PERFORMANCE: EVIDENCE FROM NIGERIAN MANUFACTURING COMPANIES - Ngozi Okoroafor, Stella; Chidinma Okoro, Theresa; Kemakolam Uzoma, Samuel (African Journal of Social and Behavioural Sciences, 2024)
The study examined the impact of Asset management ratio on the financial performance of manufacturing companies in Nigeria. Specifically, the study examines the effect of the asset Utilization Ratio, Asset Productivity Ratio and Current Asset Turnover Ratio on the Return on Assets. The study adopted the Ex-post factor research design. The main sources of data for this study were secondary sources obtained from the online publication of the annual report of eighteen Nigerian manufacturing companies quoted on the Nigerian Stock Exchange in the year 2022. A sample size of eighteen (18) manufacturing companies whose financial statements were accessible online for the year 2022 was purposely taken. The approaches used to measure asset management are asset utilization ratio, asset productivity ratio, and current asset turnover ratio, while financial performance is measured by profitability using return on assets (ROA). A linear relationship was established between the Return on Asset (ROA), the dependent variable, and the independent variables, Asset Utilization Ratio (ASUR), Current Asset Ratio (CASR) and Asset Productivity Ratio (ASPR). The Ordinary Least Square Regression Model was used to express the model relationship between ROA and the explanatory variables, ASUR, CASR and ASPR. Descriptive statistics were also employed to analyse the descriptive properties of the variables. The regression t-statistics results were used to test the hypotheses at a 5% level of significance. Findings showed that the Asset Utilization Ratio has a significant effect on Return on Asset, while the Asset Productivity Ratio and Current Asset Turnover Ratio have an insignificant effect on Return on Assets. The study recommends that manufacturing companies should improve their asset management practices in the areas of Asset Productivity Ratio and Current Assets to enhance their financial performance.